New Data on the Occurrence of Scarabaeoid Beetles (Coleoptera: Scarabaeoidea) in Montenegro - Adam Byk (Insects, 2022)
The Montenegrin fauna of the superfamily Scarabaeoidea is not satisfactorily studied. This is evidenced by the small number of species from this superfamily reported from Montenegro, despite the richness of the country’s habitats, especially high-mountain meadows, pastures, lush canyons, riverside, coastal dunes and old forests. Moreover, significant is the greater number of species of scarabaeoid beetles in neighbouring countries. Therefore, we aim to supplement the current information on the distribution of the taxa of the superfamily Scarabaeoidea in the country. The presented scarabaeoid beetles were caught during three expeditions: the first in May/June 2019, the second in May/June 2021, and the third in July 2021. As a result of this study, we have collected 2130 beetles belonging to 107 species and five families of the superfamily Scarabaeoidea: Geotrupidae, Trogidae, Lucanidae, Ochodaeidae and Scarabaeidae. The 28 days of the faunistic study confirmed the occurrence in Montenegro of 54.2% of the scarabaeoid species hitherto known from this country and added 16 new species that had not been previously recorded: Odonteus armiger (Scopoli, 1772), Trox sabulosus (Linnaeus, 1758), Ochodaeus integriceps Semenov, 1891, Agrilinus convexus (Erichson, 1848), Melinopterus reyi (Reitter, 1892), M. sphacelatus (Panzer, 1798), Phalacronothus biguttatus (Germar, 1824), Trichonotulus scrofa (Fabricius, 1787), Psammodius nocturnus Reitter, 1892, Platytomus tibialis (Fabricius, 1798), Pleurophorus mediterranicus Pittino & Mariani, 1986, P. pannonicus Petrovitz, 1961, Rhyssemus berytensis Marseul, 1878, Onthophagus ovatus (Linnaeus, 1767), Rhizotrogus aestivus (Olivier, 1789) and Chaetopteroplia segetum (Herbst, 1783). Six species and three subspecies that are typical for the Balkan Peninsula were also found: Trypocopris alpinus balcanicola (Mikšić, 1954), Onthophagus panici Petrovitz, 1964, Amphimallon solstitiale simplicissimum (Müller, 1902), Omaloplia illyrica (Baraud, 1965), Triodontella dalmatica (Baraud, 1962), Chaetopteroplia segetum straminea (Brullé, 1832), Anomala matzenaueri Reitter, 1918, Exomala adriatica (Petrovitz, 1968) and Oxythyrea dulcis Reitter, 1899. Thus, the number of currently known scarabaeoid species in Montenegro has increased to 184. Twenty-four species of scarabaeoid beetles are illustrated. Our results indicate insufficient knowledge of the Scarabaeoidea of Montenegro and, at the same time, their diversity and the presence of rare species among them. High-mountain and coastal communities of coprophagic scarabaeoid beetles, as well as communities of scarabaeoid beetles inhabiting coastal dunes, are especially valuable, worthy of protection. Therefore, further research and new expeditions to Montenegro are highly desirable.